Maladministrasi Dan Ketidak-Berdayaan - Andi Alfatih (PUBLICA, 2011)
In developed country, the public order mostly has reached the satisfying level. Public administration guarantees whatever ordered by the government will be conducted well. There must be maladministration if it is not realized. Maladministration can be defined as the failure or inability to execute the administrative jobs mannerly, equally and professionally. There is a tendency of direct or indirect disadvantages in maladministration. The failure is caused by some aspects such as careless policy made, ambiguous objective, incorrect sanction, incompetency, incompatible job, organization conflict, mismanagement, overloaded work load, and unwise expense of money. Maladministration is the practice of executing the administrative jobs by breaking the set and settled regulations. There are some serious actions to be done by the government to reduce maladministration such as employee recruitment, law enforcement, strengthening the mission accomplishment, welfare improvement, etc. There must be a transformational leader to realize this, since he will able to empower others or his subordinators. Maladministration has caused the inability for many people, and it happens in many countries, places and institutions. Lets we avoid this kind of practice.